CD8(+)-T-Cell Depletion Ameliorates Circulatory Shock in Plasmodium berghei-Infected Mice - Chang, Wun-Ling (American Society for Microbiology, 2001)
The Plasmodium berghei-infected mouse model is a well-recognized model for human cerebral malaria. Mice infected with P. berghei exhibit (i) metabolic acidosis (pH < 7.3) associated with elevated plasma lactate concentrations, (ii) significant (P < 0.05) vascular leakage in their lungs, hearts, kidneys, and brains, (ii) significantly (P < 0.05) higher cell and serum glutamate concentrations, and (iv) significantly (P < 0.05) lower mean arterial blood pressures. Because these complications are similar to those of septic shock, the simplest interpretation of these findings is that the mice develop shock brought on by the P. berghei infection. To determine whether the immune system and specifically CD8(+) T cells mediate the key features of shock during P. berghei malaria, we depleted CD8(+) T cells by monoclonal antibody (mAb) treatment and assessed the complications of malarial shock. P. berghei-infected mice depleted of CD8(+) T cells by mAb treatment had significantly reduced vascular leakage in their hearts, brains, lungs, and kidneys compared with infected controls treated with rat immunoglobulin G. CD8-depleted mice were significantly (P < 0.05) protected from lactic acidosis, glutamate buildup, and diminished HCO(3)(−) levels. Although the blood pressure decreased in anti-CD8 mAb-treated mice infected with P. berghei, the cardiac output, as assessed by echocardiography, was similar to that of uninfected control mice. Collectively, our results indicate that (i) pathogenesis similar to septic shock occurs during experimental P. berghei malaria, (ii) respiratory distress with lactic acidosis occurs during P. berghei malaria, and (iii) most components of circulatory shock are ameliorated by depletion of CD8(+) T cells.